Answer:
-1/2 = x
Explanation:
2 (x - 4) = 6x - 6 (distribute)
2x - 8 = 6x - 6 ( subtract 2x from each side)
- 8 = 4x - 6 ( add 6 to both sides)
-2 = 4x ( divide each side by 4)
x = -2/4 which simplifies to -1/2
x is -1/2 (negative one half)
Apply distributive property on the left in order to get rid of the parenthesis, and then group all terms in x on the right, and all numerical terms on the left. Combine like terms, and finally solve for "x":
2 (x - 4) = 6 x - 6
2 x - 8 = 6 x - 6
6 - 8 = 6 x - 2 x
-2 = 4 x
x = -2/4
x = -1/2
5.8m questions
7.5m answers